Proceedings of the Thirty-First SIGCSE Technical Symposium on Computer Science Education 2000
DOI: 10.1145/330908.331844
|View full text |Cite
|
Sign up to set email alerts
|

Supporting reflection in introductory computer science

Abstract: Educational theory suggests that student learning is enhanced when students pay attention to their own learning. In this paper, we describe a range of innovative techniques that we use to encourage students to reflect on the state of their knowledge, and on the process by which they acquire it. Examples include providing web-based arrangements for students to practice assessing material based on the criteria we use in marking, and allocating marks in assessment for reflective writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…In their study of learning styles and performance in an introductory programming sequence, Thomas et al (2002) found that reflective learners, who learned by thinking things through and working on their own, scored higher than active learners who learned by trying things out and working with others. To enhance student reflection in an introductory programming unit, Fekete et al (2000) incorporated different assessment strategies, and reported that, in their view, reflection enhanced the technical mastery of their students.…”
Section: Assessmentmentioning
confidence: 99%
“…In their study of learning styles and performance in an introductory programming sequence, Thomas et al (2002) found that reflective learners, who learned by thinking things through and working on their own, scored higher than active learners who learned by trying things out and working with others. To enhance student reflection in an introductory programming unit, Fekete et al (2000) incorporated different assessment strategies, and reported that, in their view, reflection enhanced the technical mastery of their students.…”
Section: Assessmentmentioning
confidence: 99%
“…Reflection over software development process [35]; questioning and evaluation of process; open-ended problem-solving and design [36]. challenges faced by educators within this space, supporting the adoption of pedagogy based around explicit sharing of mental models, and guided discovery techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Our main goal was to encourage and support reflection activities. Not so much reflection on the learning process where a reflective diary might be more appropriate [6], but reflection on programming related concepts, constructs, examples etc. ; and the way they are understood and can be further employed.…”
Section: Discussion and Future Plansmentioning
confidence: 99%